2003
DOI: 10.3354/meps265283
|View full text |Cite
|
Sign up to set email alerts
|

Increased blooms of a dinoflagellate in the NW Atlantic

Abstract: Sampling by the Continuous Plankton Recorder (CPR) over the NW Atlantic from 1960 to 2000 has enabled long-term studies of the larger components of the phytoplankton community, highlighting various changes, particularly during the 1990s. Analysis of an index of phytoplankton biomass, the Phytoplankton Colour Index (PCI) has revealed an increase over the past decade, most marked during the winter (December to February) months. Examination of the structure of the community using multiple linear-regression models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 22 publications
4
12
0
Order By: Relevance
“…Most phytoplankton taxa have been consistently identified and enumerated since 1958. The PCI has been extensively used to describe the seasonal and long-term patterns of phytoplankton abundance (Reid 1978, Batten et al 2003, Johns et al 2003 in various regions of the North Atlantic. An increasing trend in phytoplankton biomass has been shown in the North Sea and in the area west of the British Isles .…”
Section: Introductionmentioning
confidence: 99%
“…Most phytoplankton taxa have been consistently identified and enumerated since 1958. The PCI has been extensively used to describe the seasonal and long-term patterns of phytoplankton abundance (Reid 1978, Batten et al 2003, Johns et al 2003 in various regions of the North Atlantic. An increasing trend in phytoplankton biomass has been shown in the North Sea and in the area west of the British Isles .…”
Section: Introductionmentioning
confidence: 99%
“…An advantage offered by this genus is that identification to species level is more feasible than for other phytoplanktonic groups, where it can be limited by the small size of the organisms or may require the use of electron microscopy and molecular tools. Moreover, Ceratium species are known to be sensitive to temperature in terms of biogeography (Dodge & Marshall 1994), seasonality and morphology (Sournia 1967), and have hence been proposed as biological indicators of water masses (Dodge 1993, Okolodkov 1996, Ochoa & Gómez 1997, Sanchez et al 2000, Raine et al 2002, current regimes (Dowidar 1973) and climate change (Dodge & Marshall 1994, Johns et al 2003. In the northwestern Mediterranean Sea, the genus is species-rich and often dominates the armoured dinoflagellates in terms of abundance (Tunin-Ley et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The Ceratium species are known from warm waters of the Tasman Sea (Hallegraeff et al 2010) and, considering the season, we suggest that the strengthening EAC was responsible for their appearance in southern Tasmania. The poleward extension of tropical and warmtemperate Ceratium species has been well documented in the Northern Hemisphere (Dodge and Marshall 1994;Johns et al 2003;Barnard et al 2004;Hays et al 2005;Edwards et al 2006), and it is predicted that subsequent expansions will occur into the future (Turin-Ley et al 2009). As Tasmania is expected to experience continued ocean warming into this century (Ridgway and Hill 2009), it follows that introductions of Ceratium, and perhaps other warm water species, will also be observed.…”
Section: Discussionmentioning
confidence: 99%
“…However, specific examples of the impacts to fisheries that stem from recorded expansions of Ceratium species are in their infancy. One notable example from Johns et al (2003) concluded that the apparent displacement of diatoms due to the significant increase in C. arcticum in the North Sea, first noted in the 1990s, played a key role in the collapse of the Atlantic Cod fishery in the Grand Banks region of east Canada. This hypothesis is well supported (e.g., Beaugrand et al 2003;Beaugrand 2004;Hays et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation